2021
DOI: 10.3389/fpls.2021.643560
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Cyclic Nucleotides and Calcium Signaling Pathways in Plants–Achievements and Prospects

Abstract: A variety of plant cellular activities are regulated through mechanisms controlling the level of signal molecules, such as cyclic nucleotides (cNMPs, e.g., cyclic adenosine 3′:5′-monophosphate, cAMP, and cyclic guanosine 3′:5′- monophosphate, cGMP) and calcium ions (Ca2+). The mechanism regulating cNMP levels affects their synthesis, degradation, efflux and cellular distribution. Many transporters and the spatiotemporal pattern of calcium signals, which are transduced by multiple, tunable and often strategical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Previous reports have shown that the activity of plant transmembrane GCs called moonlight proteins can be modulated by calcium ions [28][29][30]. In vitro experiments have shown that the GC activity of the phytosulfokine receptor AtPSKR1 is significantly enhanced by calcium at physiological levels (0.1-10 µM), and more impor-tantly, the same concentration of Ca 2+ that activates GC activity also exerts an inhibitory effect on kinase activity [31].…”
Section: In Vitro Analysis Of the Gc Activity Of Wild-type Bderl1mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that the activity of plant transmembrane GCs called moonlight proteins can be modulated by calcium ions [28][29][30]. In vitro experiments have shown that the GC activity of the phytosulfokine receptor AtPSKR1 is significantly enhanced by calcium at physiological levels (0.1-10 µM), and more impor-tantly, the same concentration of Ca 2+ that activates GC activity also exerts an inhibitory effect on kinase activity [31].…”
Section: In Vitro Analysis Of the Gc Activity Of Wild-type Bderl1mentioning
confidence: 99%
“…7A). In plants, calcium may directly or indirectly regulate protein kinases [30,40], while bioinformatics and in vitro analyses have also revealed the presence of a calmodulin-binding motif within the kinase domains of AtPSKR1 and AtBRI1; thus, it is conceivable that calcium may modulate the cyclase/kinase activities indirectly via CaM isoforms [23,31]. However, although Ca 2+ significantly inhibited the kinase activity of BdERL1, there was no significant difference in its activity with the addition of calcium alone or with the addition of both calcium and calmodulin, as both of these conditions inhibited the kinase to a similar extent (Fig.…”
Section: In Vitro Analysis Of the Kinase Activity Of Wild-type Bderl1mentioning
confidence: 99%
“…In plants, calcium 2 of 31 is an essential nutrient, and intracellular changes in free Ca 2+ levels act as regulators in many growth and developmental processes and coordinate responses to developmental cues and environmental stimuli [5,6]; in contrast, recent advances support that cAMP (and cGMP) constitutes an important component of the complex signaling network, including key pathways mediated by hormones, lipid, sugar, Ca 2+ , K + , nitrate, etc. [7][8][9][10][11][12]. Thus, it is anticipated that CNGCs may play pivotal roles during growth and development in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NO, a negative chemoattractant of pollen tube guidance, together with ROS, a positive regulator of tip growth, were shown to be required for the pollen tube elongation to the right direction [ 19 , 20 ]. These findings, together with multitasked feature of ROS, Ca 2+ , and NO [ 2 , 21 , 22 , 23 , 24 ], suggest that these signaling molecules might govern the reproductive development by regulating various other pathways.…”
Section: Introductionmentioning
confidence: 99%